Pengaruh Jumlah Dewan Direksi dan Dewan Komisaris, Ukuran Perusahaan, dan Penerapan Good Corporate Governance (GCG) terhadap Nilai Perusahaan pada Sektor Industri Dasar dan Kimia yang Terdaftar di Bursa Efek Indonesia Periode 2020-2021 - Pricilla Deby Agustina (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Company value is a form of calculation that shows how good and significant the management performance and company growth is. In Indonesia, companies in the materials and chemical industry sector have great potential because the raw materials in this industry are natural resources. In this way, investors will be interested in investing in companies in this industry in Indonesia because the possibility of company development in this sector is very high. Various factors can influence the increase in company value, including the number of board of directors, number of board of commissioners, company size, and the implementation of Good Corporate Governance (GCG). This research was conducted to ascertain the influence of these four factors partially and simultaneously on company value. This research utilizes data from the annual and financial reports of 56 companies in the basic and chemical industries in the 2020-2021 period. The results of this research indicate that the number of board of commissioners partially influences company value, while the number of board of directors, company size, and the implementation of Good Corporate Governance (GCG) partially do not influence company value. However, the number of board of directors, number of board of commissioners, company size, and implementation of Good Corporate Governance (GCG) simultaneously have an influence on company value.